Co-developing cropping scenarios for climate resilience and groundwater sustainability: a participatory scenario development method for Nalanda, Bihar - Chakraborty, Shreya; Laing, Alison; Mizan, Syed Adil; Kumar, Anurag; Sikka, Alok; Urfels, Anton; Krupnik, Timothy J. (TAFSSA, 2023)
The One CGIAR Initiative TAFSSA (Transforming Agrifood Systems of South Asia) prioritizes interdisciplinary farm and landscape level research including an assessment of groundwater availability and sustainable use under scenarios of climate change scenarios and crop diversification. To integrate groundwater and cropping system modelling participatory practices were used to identify potential cropping scenarios in Nalanda, Bihar, through bottom-up exercise in a one-day workshop. This brief presents the methods and findings of this scenario development workshop.